Carbonate free bulk analysis from IODP Core 339-U1389A-25X - Dorrik A V Stow; Zeinab Smillie; Jonathan Wilkin; Jiawei Pan; Onoriode Esegbue; André Bahr; Emmanuelle Ducassou (PANGAEA, 2024)
Grain-size statistical parameters were calculated using Gradistat software (Blott and Pye, 2001) and based on the geometric graphical method (Folk and Ward, 1957). The same samples were then treated to remove the biogenic carbonate and siliceous components, and re-analysed with the laser micro-granulometer, with a view to determining the sortable silt component.
In: Stow, DAV et al. (2024): Sediment and geochemistry of bi-gradational contourite sequences from the Gulf of Cadiz [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937307